Church, Economy and the Question of Horizons - van den Hoogen, Toine (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2010)
This paper analyses why theology has to develop a concern with economy and economics and elaborates a perspective for a new debate between theologians and economists about socio-ethical problems in public life. The hermeneutically reflected relationship between church and economic life has been elaborated in a number of principles of community development. Church and economy are seen as two important ‘horizons of human life’. Economic developments, symptoms of crisis and symptoms of stagnation are mainly present in the Church’s social teaching owing to the fact that faith communities and their leaders are confronted with these social problems. This paper approaches the relationship between the two horizons in a perspective of public theology. An open conversation between theology and economics focuses on a new praxis-led theology. Whenever the meaning of ‘the good life’ is attached to the realisation of functions and capacities in the concrete markets within an actual economy, the actuality of the economic reality is placed within a horizon that expresses a sense of that life. It then becomes possible to state that a concrete set of functions and capacities are in service to humanity. Keywords:*community development, *'telos', *public theology, *spirituality, *institution *globalisation *contextualisation, *normative economics, *human dignity, *economics for the common good, *'bonum commune' *good life